Effect of Complementary Medicine on Pain Relief and Wound Healing after Cesarean Section: A Systematic Review - Azin Niazi; Maryam Moradi; Vahid Reza Askari; Neda Sharifi (Korean Pharmacopuncture Institute, 2021)
Objectives: Cesarean sections are one of the common surgical procedures around the world. Management of cesarean section side effects, including pain, hematoma, delayed wound healing, is of particular importance in maintaining maternal health and ability to care for the baby. The tendency to use complementary medicine strategies is on the rise because of the easy treatment with low side effects. The purpose of this study was to systematically review the efficacy and safety of clinical trials performed in Iran and worldwide on the effect of complementary medicine on pain relief and wound healing after cesarean section.Methods : : PRISMA checklist was followed to prepare the report of this systematic review. The search process was carried out on databases on databases of Magiran, SID, Iran Medex, Scopus, Pub Med, Science direct, Medline and Cochrane library using keywords of cesarean, pain, wound healing, Herbal medicine, acupressure, massage, complementary medicine and their Persian equivalent and all possible combinations, from inception until February 2020. We used the Jadad scale to assess the quality of the searched articles. According to the Jadad scale, the articles with a score of at least 3 were included in the study.Results : : Finally, 28 clinical trials (with a sample size of 3,245) scored at least 3 on the Jadad scale were included into the analysis. This article reviewed 13 articles on medicinal herbs, 4 articles on massage, 1 article on reflexology, 2 articles on acupressure.Conclusion : : According to the present review, the use of medicinal herbs was the most common method of complementary medicine in pain relief and wound healing after cesarean section.